Proposed Design of Wind Turbine for Highway Energy Harvesting - Ahmad Danial Ezman Bin Azhar; Rosly, Nurhayati (Progress in Aerospace and Aviation Technology, 2025)
This study explores the feasibility of deploying wind turbines alongside highways to harvest untapped wind energy generated by vehicular traffic, with a focus on Malaysia's North-South Highway. The research aims to analyze local wind meteorology data, identify suitable wind turbine designs for roadside applications, and propose mechanically optimized configurations to enhance energy harvesting efficiency and safety. The methodology involves a comprehensive literature review on wind patterns, structural considerations, and turbine types from international contexts, followed by the simplification and design of vertical axis wind turbines (VAWTs), specifically Darrieus and Savonius models, using SolidWorks software. Computational fluid dynamics (CFD) simulations were conducted at a wind speed of 30.56 m/s (equivalent to Malaysia's highway speed limit of 110 km/h), evaluating parameters such as blade count, materials (e.g., high-grade steel alloys), airflow density, pressure, velocity, and power output. Data from the Malaysian Meteorological Department (2019–2022) informed site-specific assessments, particularly for the Pagoh to Yong Peng section. Findings indicate that VAWTs are most appropriate for highway installations due to their adaptability to turbulent, low-speed winds. The Darrieus turbine outperformed the Savonius and a previous design, achieving an average velocity of 27.460 m/s, a pressure of 101797.48 Pa, and a power output of 3.163 kW, exceeding the Betz limit of 1.875 kW and demonstrating superior energy capture efficiency. This research contributes to renewable energy integration in transportation infrastructure by providing evidence-based recommendations for VAWT deployment, highlighting mechanical optimizations for safety and performance. It informs policymakers, engineers, and developers on sustainable practices, potentially reducing reliance on fossil fuels while enhancing highway energy self-sufficiency.